1990
DOI: 10.1152/ajpheart.1990.258.1.h191
|View full text |Cite
|
Sign up to set email alerts
|

Preload does not affect relaxation rate in normal, hypoxic, or hypertrophic myocardium

Abstract: To determine whether isolated changes in preload (end-diastolic force) can influence myocardial relaxation rate in normal or abnormal (hypoxic or hypertrophic) hearts, isolated LV papillary muscles from normal Wistar-Kyoto (WKY) and spontaneously hypertensive (SHR) rats were studied using physiologically sequenced contractions. While total (systolic) load and late (lengthening) load were held constant, maximum isometric force decline (peak -dT/dt) and maximum isotonic lengthening rate (peak +dL/dt) were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In such situations, the systolic pressure (SP) developed during the contractions and the +dp/dt Have Been accepted as parameters of systolic function [11][12][13] . In the same way, -dp/dt has been used as a parameter of diastolic function 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In such situations, the systolic pressure (SP) developed during the contractions and the +dp/dt Have Been accepted as parameters of systolic function [11][12][13] . In the same way, -dp/dt has been used as a parameter of diastolic function 14 .…”
Section: Discussionmentioning
confidence: 99%
“…It may be surmised from a further unpublished observation we have made that increasing LVEDP diminishes τ at small LVEDP but increases it rapidly at very high LVEDP, whereas τ is only slightly affected in a range of moderate LVEDP, such as in the present protocol. In hypoxic or hypertrophic rat myocardium, preload also has not affected the relaxation rate considerably [27].…”
Section: Lusitropic Effects Of Hemodynamic Changesmentioning
confidence: 92%
“…In other studies reporting prolonged τ when LVEDP was increased, LVP max was not kept constant but also allowed to increase [4 (protocol B), 7,16]. Experimental methods to manipulate LVEDP and to calculate τ that are different from that presently adopted showed no or almost insignificant lusitropic LVEDP effects in dogs, rabbits, and humans [9,21,24,27].…”
Section: Lusitropic Effects Of Hemodynamic Changesmentioning
confidence: 99%
“…Afterload elevations exceeding the relative load of the transition (80, 90, and 100% interventions) progressively slowed the rate of LVP fall, with the amount of slowing increasing from low to mid preload but not changing from mid to high preload. Previous studies reported contradictory effects of preload on rate of LVP fall, with some authors describing a decrease in relaxation rate (5,9,29,36) and others describing no effects (35,39) in response to preload elevations. Some of these discrepancies were attributed to the concomitant changes in preload and afterload in response to the majority of interventions used to modify preload (e.g., volume infusion and caval occlusions).…”
Section: Load and LV Relaxationmentioning
confidence: 99%